2005
DOI: 10.3152/147154305781779588
|View full text |Cite
|
Sign up to set email alerts
|

Public values and public failure in US science policy

Abstract: Domestic science policy in the United States is linked inextricably to economic thinking. We seek to develop a practical analytical framework that confronts the manifest problems of economic valuing for science and technology activities. We argue that pervasive use of market valuation, market-failure assumptions and economic metaphors shapes the structure of science policy in undesirable ways. In particular, reliance on economic reasoning tends to shift the discourse about science policy away from political qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 50 publications
1
70
0
8
Order By: Relevance
“…First, as Bozeman and Sarewitz (2005) argue, the potential societal benefits imagined by individual scientists might not necessarily be desired by the rest of society. In addition, one interesting study looked at variables that impact eventual utilization of research results, and found no correlation between researchers' focus on users' needs and the likelihood of knowledge utilization (Landry, Amara, and Lamari 2001).…”
Section: Does "Use-inspired" Research Promote Greater Societal Benefit?mentioning
confidence: 99%
See 2 more Smart Citations
“…First, as Bozeman and Sarewitz (2005) argue, the potential societal benefits imagined by individual scientists might not necessarily be desired by the rest of society. In addition, one interesting study looked at variables that impact eventual utilization of research results, and found no correlation between researchers' focus on users' needs and the likelihood of knowledge utilization (Landry, Amara, and Lamari 2001).…”
Section: Does "Use-inspired" Research Promote Greater Societal Benefit?mentioning
confidence: 99%
“…The question of which users to invite to the table is difficult. Science policy scholars have recommended public participation in merit review (Bozeman and Sarewitz 2005;Guston 2004). Alternatively, Frodeman and Holbrook (2007) suggested inviting both experts in education and public outreach and researchers on science, technology, and society to participate on the merit review panel to judge the broader impacts.…”
Section: Modifying the Merit Review Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, deja claro que esta "justicia distributiva" debe llegar a transformarse en una serie de valores públicos (Bozeman y Sarewitz, 2005) con miras a consolidar una ciencia democrá-tica, que tome en consideración los problemas y las visiones de "los de abajo" (Woodhouse y Sarewitz, 2007) y donde la comunidad político-científica (Granados y Viales, 2013) (conjunto de actores políticos que formulan políticas científicas y tecnológicas, y que toman decisiones en esta materia) considere el criterio de los científicos como expertos (Viales, Arellano y Granados, 2012), para construir políticas de alcance nacional, regional y local (Bhushan, 2015 Si bien, la relación entre Ciencia y Sociedad es intrínseca, lo que sí ha cambiado es la historicidad de la relación, es decir, la manera en que se han vinculado ambos campos y la forma en que se ha interpretado esa relación, en distintas épocas y en espacios históricos diferentes.…”
Section: ¿Qué Es La Cohesión Social Y Cuál Es Su Relación Con Las Polunclassified
“…The Public Value Mapping (PVM) of Science Outcomes is a conceptual tool that aims to comprehend causes of social outcomes (Bozeman, Sarewitz, 2005). Outcomes stand for changes in the behaviors, relationships, activities and/or actions of the stakeholders (Earl et al, 2001).…”
Section: Literature Review On Qualitative Methods For Evaluating Isripmentioning
confidence: 99%